The Effect of Grape Pomace Fiber Addition on Quality Parameters of Yogurt - Ahmet Ayar; Hatice Sıçramaz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Reducing food and industrial waste is essential to match the novel objectives of sustainable living. In this context, grape pomace, a fiber-rich by-product of wine production, was used as a fiber supplement in yogurt after enriching its fiber content through preprocessing. Within the aim of this study, 0.5% and 1% grape pomace fiber were incorporated into yogurt, and the effect on physicochemical, microbial, and sensory quality was investigated. Throughout the 14-day storage period, no significant changes were observed in pH, acidity, and water holding capacity. The total mesophilic aerobic bacteria count ranged between 2-3 log.cfu/g, and the addition of fiber did not result in any undesirable alterations in these counts. Similarly, the fiber did not affect the counts of specific yogurt bacteria, which was 8-9 log.cfu/g. Moreover, sensory evaluations consistently resulted in scores above “5” for all products, with acidity rated level as moderate as expected for yogurt. There were no adverse effects on sensory quality concerning color, flavor, texture, acidity, and overall acceptability. In conclusion, fiber-enriched yogurt from wine waste is feasible without compromising product quality. This study is expected to contribute to the progress of current sustainable living goals.